Challenges of Teaching Science to Address Global Sustainability - Halim, Lilia (Prosiding KPSDA, 2015)
For a liveable condition in this post- industrial era, it would depend on our ability to understand and use the science and technology advancement in a responsible manner. Water pollution and global warming phenomena are outcomes of scientific and technological advancement that has been mismanaged. One way to achieve global sustainability is through science education and the development of a scientific literate citizen. This paper, based on the literature and research work in science education in Malaysia, outlines how scientific literate citizen can address global sustainability, assess the level of scientific literate of Malaysian students and discuss the challenges in teaching science to develop scientific literacy and hence global sustainability.